Antibacterial activity of nano-hydroxyapatite paste of snakehead fish bone against S. mutans: an in vitro study - Dewi, Nurdiana; Rahmadella, Afifah; Hatta, Isnur; Apriasari, Maharani Laillyza; Putri, Deby Kania Tri (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Caries is the most common oral disease found in society. The prevalence of caries in South Kalimantan is as high as 46.9% in 2018. S.mutans is the causative microorganism in the  initial occurrence of caries. Strategy that can be used to prevent caries is by adding nano-hydroxyapatite to the tooth paste. Nano-hydroxyapatite can be obtained from Snakehead (Channa striata) fish bone.  Snakehead is a kind of fish that is abundant in Banjarmasin.  This study aimed to analyze antibacterial activity of the nano-hydroxyapatite paste from snakehead (Channa striata) fish bone against S.mutans bacteria. Methods: The study consisted of 5 treatment groups: negative control (basic formula), positive control (casein phosphopeptide-amorphous calcium phosphate or CPP-ACP) and three treatment groups (nano-hydroxyapatite paste concentration of 10, 20 and 30%. The paste was made in the formulation of F1, F2, and F3. The antibacterial activity test by measuring MIC and MBC were performed using dilution method. Results: MIC of nano-hydroxyapatite paste was at a concentration of 10% with an average value of the difference absorbance of -0.468. MIC values in the concentration of 10%, 15%, 20% positive and negative control groups had a significant difference. MBC of nano-hydroxyapatite paste was at concentration of 15%. Concentration of 10% and the negative control group showed a significant difference, while concentration of 15% and 20% groups did not show a significant difference. Conclusion: Nano-hydroxyapatite paste from Snakehead fish bone has antibacterial activity in inhibiting and eliminating mutated S.mutans bacteria. The most effective concentration of antibacterial nano-hydroxyapatite paste to prevent caries was 10%. At this concentration, nano-hydroxyapatite can inhibit the growth of S.mutans without killing the bacteria.KEYWORDS fish bone, nano-hydroxyapatite, snakehead, S.mutans